1999
DOI: 10.1046/j.1365-2567.1999.00775.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathogenesis of classical swine fever: role of monocytic cells

Abstract: SUMMARYVirulent classical swine fever (CSF ) represents an immunomodulatory viral infection that perturbs immune functions. Circulatory and immunopathological disorders include leukopenia, immunosuppression and haemorrhage. Monocytic cells -targets for CSF virus (CSFV ) infection -could play critical roles in the immunopathology, owing to their production of immunomodulatory and vasoactive factors. Monocytes and macrophages (Mw) are susceptible to virus infection, as a consequence of which prostaglandin E 2 (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 23 publications
1
67
0
Order By: Relevance
“…Indeed, TNF-α and IFN-α can have adverse effects when produced in huge amounts after viral infection [32]. Thus, it was suggested that TNF-α secreted by CD172a + cells, together with IL-1, IL-6 and prostaglandin, were responsible for apoptosis in non-infected immune system cells in lymphoid organs [16,24,38]. These authors implicated macrophages as TNF-α producing cells, but our data showed that DC could also play a role in this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, TNF-α and IFN-α can have adverse effects when produced in huge amounts after viral infection [32]. Thus, it was suggested that TNF-α secreted by CD172a + cells, together with IL-1, IL-6 and prostaglandin, were responsible for apoptosis in non-infected immune system cells in lymphoid organs [16,24,38]. These authors implicated macrophages as TNF-α producing cells, but our data showed that DC could also play a role in this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Cell associated virus was released by sonificating the cells and clarification of the cell lysates as described [17]. For mock controls, clarified lysates of uninfected cells were employed.…”
Section: Virusmentioning
confidence: 99%
“…For mock controls, clarified lysates of uninfected cells were employed. Virus titres were determined by endpoint dilution titrations on SK-6 cells as described previously [17].…”
Section: Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…MoDC cultures were pulsed with the following antigens for 26 h, with Ctx added after 2 h if required: (1) CSFV strain Alfort (0.01 TCID 50 /cell), (2) mock antigen prepared from uninfected SK6 cells used to propagate the virus [27], (3) E2-protein of CSFV, baculovirus-expressed (4 µg/mL) produced as described elsewhere [36], or (4) CSFV-non-structural protein 3 (NS3)-protein of CSFV, E. coli-expressed (2 µg/mL; kindly provided by Dr Hilde Revets, Free University Brussels, Belgium). MoDC were then co-cultured with autologous lymphocytes in the presence of the respective antigens for 3-4 days, and analysis of [ 3 H]methyl-thymidine incorporation was performed as described above.…”
Section: Modc Proliferation Assaysmentioning
confidence: 99%